ANALYSIS OF JOB CHARACTERISTICS, JOB SATISFACTION AND PATIENT SAFETY CULTURE AMONG HEALTHCARE (STUDY IN MUHAMMADIYAH UNIVERSITY GENERAL HOSPITAL OF MALANG) - Paripih, Wirasasmita; Martiana, Tri (Universitas Airlangga, 2024)
Background Job satisfaction is a combination of feelings towards his job, both happy and unhappy, as a result of interaction with the work environment. Job satisfaction can have a significant influence on patient safety culture. The purpose of this study was to analyse job characteristics, employee job satisfaction, and patient safety culture in health workers at the Muhammadiyah University General Hospital of Malang. Method This research was analytic observational research with a cross-sectional design. The sample was 144 health workers obtained from 202 people through simple random sampling. The HSOPS questionnaire version 2.0 to measure patient safety culture consists of 10 dimensions, and the MMSS questionnaire to measure job satisfaction consists of 8 dimensions. Data was analysed using structural equation modelling with Smart PLS 3.0 software. Result The result showed that there was an influence of job characteristics on job satisfaction (T-statistic = 3,472 > 1.96) with a coefficient value of -0,333, which means doctor had higher level of job satisfaction than nurse, midwife, pharmacist, and other health workers. Job satisfaction affected patient safety culture (T-statistic = 5.359 > 1.96) with a coefficient value of 0,451, the higher the level of job satisfaction, the higher the level of patient safety culture. Conclusion The conclusion of this study was that there was an influence of job characteristics and job satisfaction. Job satisfaction influenced patient safety culture among health workers. Patient safety culture need to be improved by strengthening the dimensions of employees and work rates, responding to errors, and reporting patient safety events. To improve job satisfaction, it was necessary to strengthen the dimensions of work-family balance and scheduling.